The effectiveness of using the complex fertilizers on crops of a high-lysin corn variety named uzbekistan 420 vl - Yejov Maksim Nikolaevich; Audu, Akhmedov Jamalkhan Khujakhanovich; Akhmedov Zhabbarkhan Jamalkhanovich; Obijoniov Jasurbek Obidjonovich (Research Parks Publishing LLC, 2021)
In this article given information and discuss about the effect of the rates of mixed fertilizers on grain yield and the total content of protein and lysine in protein, fertilizer rates and plant density per hectare